2019
DOI: 10.18203/2320-6012.ijrms20194326
|View full text |Cite
|
Sign up to set email alerts
|

Fungal infections in patients with chronic liver disease: mortality and associated risk factors

Abstract: Background: Patients with chronic liver disease are immunocompromised and prone to different opportunistic infections. Fungal infections in patients admitted with liver cirrhosis are not rare and they may increase mortality and morbidity of these patients. Aims of the study is to determine the mortality and its risk factors associated with fungal infections in patients with chronic liver disease.Methods: In this retrospective study, patients admitted with chronic liver disease during the last four years on thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 22 publications
(27 reference statements)
1
9
0
Order By: Relevance
“…Bassetti et al reported that, in 169 patients with fungal infection, 46% of patients were infected with non‐candida species, and 35% of mortality was linked to candida infection and absent or inadequate antifungal treatment 22 . Rasool et al 23 reported renal insufficiency as one of the predictors of mortality in fungal infections in CLD patients, and similar findings were observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Bassetti et al reported that, in 169 patients with fungal infection, 46% of patients were infected with non‐candida species, and 35% of mortality was linked to candida infection and absent or inadequate antifungal treatment 22 . Rasool et al 23 reported renal insufficiency as one of the predictors of mortality in fungal infections in CLD patients, and similar findings were observed in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Population was reported mainly into three categories, that is ICUadmitted cirrhosis (nine studies), 35,[44][45][46][47][48][49][50]57 hospitalised-ACLF (eight studies) 12,13,[51][52][53][54][55][56] or all-hospitalised cirrhosis with admission area not specified (17 studies). [26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43] Eighteen, eight and eight studies examined proven, 26,28,[31][32][33][35][36][37]39,[41][42][43]45,46,48,50,…”
Section: Descriptive Synthesismentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43] Eighteen, eight and eight studies examined proven, 26,28,[31][32][33][35][36][37]39,[41][42][43]45,46,48,50,51,57 probable 29,30,34,38,47,49,55,56 and proven+probable FIs, 12,13,27,40,44,[52][53][54] respectively. Studies emanated from Europe (15 studies) , 12,…”
Section: Descriptive Synthesismentioning
confidence: 99%
See 2 more Smart Citations